2013
DOI: 10.4236/aim.2013.33036
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis and Correlates in Women of Reproductive Age in Thika, Kenya

Abstract: Background: Bacterial vaginosis (BV) is the most common cause of abnormal vaginal discharge among women of childbearing age which is associated with STI/HIV and adverse birth outcomes. The Main objective of this study was to determine the prevalence and correlates of BV among women of reproductive age in Thika. Methods: Between July 2010 and February 2011, 193 women of reproductive age (18 -49 years) were enrolled from family planning and ante-natal clinics in Thika District Hospital, Kenya. The study was desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
7
2
2
Order By: Relevance
“…There is no specific color of vaginal discharges for the diagnosis of BV; experts varied in opinion but it is important to know that women with BV present abnormal vaginal discharges and the vaginal discharges differ in the consistency, Garba et al [ 21 ]. Abdominal pain and itching symptoms were found in 26.6% and 23.2%, respectively, which was consistent with the result reported by Nzomo et al [ 30 ] in Kenya. This study registered no significant relationship between abdominal pain, itching, and BV.…”
Section: Discussionsupporting
confidence: 91%
“…There is no specific color of vaginal discharges for the diagnosis of BV; experts varied in opinion but it is important to know that women with BV present abnormal vaginal discharges and the vaginal discharges differ in the consistency, Garba et al [ 21 ]. Abdominal pain and itching symptoms were found in 26.6% and 23.2%, respectively, which was consistent with the result reported by Nzomo et al [ 30 ] in Kenya. This study registered no significant relationship between abdominal pain, itching, and BV.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to effects of factors such as altered menstrual status, hormonal changes, sexual activity, contraceptive use and pregnancy in females of these age groups which may have contributed for higher risk of vaginal infection. Similar finding has been reported by Nzomo et al [10] in their study conducted in Kenya. Majority of the patients were from rural area and unemployed with low family incomes.…”
Section: Discussionsupporting
confidence: 81%
“…Laxmi et al, in their review on infectious vaginitis inform that bacterial vaginosis has been found to be more common among the women of reproductive age group [8]. A similar finding was obtained in a range of other studies [9,10]. In our study, itching/soreness of genital organ was most frequent complaint of females with vaginitis followed by discharge from genitals accompanying with unpleasant odor, burning micturition, discomfort during intercourse.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies explained the factors that responsible for the low percentage of candidiasis infection in old women like the reduced effect of estrogen hormone, reaching menopause, less or no sexual activity, no contraceptive, and also have good vaginal immunity because they have low estrogen and corticoids (Nelson et al, 2013). BV was higher in age group 32-38 years and this present result agree with the finding of (Nzomo et al, 2013) followed by (25)(26)(27)(28)(29)(30)(31) years. It is worthwhile to mention these age groups represent the peak of child bearing ages and also may attributed to high sexual activity.…”
Section: Progesterone and Estrogens Have Direct Effects Onsupporting
confidence: 89%